Designing a CXCL8-hsa chimera as potential immunmodulator of the tumor micro-environment - Gerlza, Tanja; Trojacher, Christina; Fuchs, Thomas; Atlic, Aid; Weis, Roland; Adage, Tiziana; Kungl, Andreas J. (Frontiers in Immunology, 2025)
IntroductionCXCL8, belonging to inflammatory chemokines, is expressed by various cell types and plays a key role in leukocyte trafficking during infections, inflammatory processes, tissue injury and tumor progression. Chemokines interact not only with G-protein coupled receptors but also with glycosaminoglycans (GAGs), which are polyanionic linear polysaccharides. Chemokine-GAG interactions are critical for creating localized concentration gradients, protecting chemokines from degradation, and maintaining their efficacy in vivo.MethodsWe have previously engineered a CXCL8-based dominant-negative decoy (“PA401”) with strongly increased GAG binding affinity combined with complete GPCR knockout, which was originally developed for the treatment of COPD. Here we have optimized our engineering protocol by minimizing CXCL8 mutations while conserving its in vitro dominant-negative activities. This novel CXCL8-based decoy (mtCXCL8) was further fused to human serum albumin (HSA) to overcome the typically very short serum half-life of chemokine-based biologics. We are therefore able to present here an entirely novel CXCL8-based biologic (hsa/mtCXCL8) which reflects our threefold modification strategy – increasing GAG-binding affinity by minimal mutagenesis, GPCR knockout, and fusion to HSA – thus representing a comprehensive and novel approach towards addressing chronic CXCL8-driven diseases.ResultsIn the current study, we have investigated the immunomodulatory potential of our new decoy in a 3-D cellular tumor model (“BioMAP”) which relates the biomarker interaction profile of immune and tumor cells to a data-base mirrored biomarker read-out. The obtained BioMAP results suggest an impact of hsa/mtCXCL8 on the immune compartment of the VascHT29 cell model by modulating cytokine levels and inhibiting immune cell activation markers. When combined with Keytruda (Pembrolizumab), a PD-1 inhibitor, it enhances some of its known activities, indicating potential synergistic effects, but further investigation is needed due to the observed increase in soluble IL-6 and limitations in dose selection for future in vivo studies.DiscussionBy prolonging the presence of engineered chemokine mutants in the bloodstream and optimizing their stability, these strategies aim to enhance the therapeutic efficacy of CXCL8-based interventions, offering promising avenues for the treatment of several CXCL8-mediated pathologies, including cancer.